TINGKAT PARTISIPASI MASYARAKAT DALAM PENGELOLAAN HUTAN KEMASYARAKATAN: Studi Kasus Gabungan Kelompok Tani Sinar Hala, Desa Lewohala, Kecamatan Ile Mandiri, Kabupaten Flores Timur - Desi Ferderika Nalle; Ludji Michael Riwu Kaho; Astin Elise Mau (MARSEGU : Jurnal Sains dan Teknologi, 2026)
Level of community participation in the stages of Community Forest (HKm) management, including planning, implementation, utilization, and evaluation/monitoring. This research was carried out in Lewohala Village, Ile Mandiri District, East Flores Regency, which is an area with an HKm program implemented through the Sinar Hala Farmers Group Association (Gapoktan). The results of study indicate that the participation of the Sinar Hala Community Forest Farmers Group Association was relatively low in the planning stage of Community Forestry (46.75%), and also low in the monitoring and evaluation stage (25%). This is attributed to the community's lack of awareness regarding the importance of forest management and the absence of strong group institutionalization.Conversely, community participation was found to be high in the implementation stage of Community Forestry (62.76%) and in the utilization stage (63.59%). This high participation is due to the community managing the HKm area by planting plantation, food, and horticultural crops, the yields of which are used for both consumption and sale. These findings suggest that community participation is significantly influenced by direct economic benefits and the importance of strengthening institutional capacity to support the sustainability of the HKm program. This research is expected to serve as evaluation material for the Forest Management Unit (KPH) and local government in enhancing the effectiveness of community-based forest management.